1985
DOI: 10.1038/318154a0
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis and human T-cell lymphotropic retroviruses

Abstract: A combination of different types of data suggests that some multiple sclerosis patients respond immunologically to, and have cerebrospinal T cells containing, a retrovirus that is related to, but distinct from, the three types of human T-cell lymphotropic viruses. The role of this virus in multiple sclerosis is uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
102
2
9

Year Published

1986
1986
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(116 citation statements)
references
References 29 publications
3
102
2
9
Order By: Relevance
“…Our failure to demonstrate serological evidence for exposure to HTLV I and III (HIV) in patients with multiple sclerosis contrasts with the findings of Koprowski et al [5] but is in agreement with more recent results [1,4,7,8]. Although they are regarded as reliable indicators of HTLV exposure in population screening, Koprowski et al [6] suggest that commercial ELISA tests against disrupted virions are insensitive cornOffprint requests to: D. A. S. Compston pared with assays detecting antibody to the major core protein p24 of HTLV I alone because the antibodies are present in low titre, cross-reactive and only present sporadically in the course of the disease.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…Our failure to demonstrate serological evidence for exposure to HTLV I and III (HIV) in patients with multiple sclerosis contrasts with the findings of Koprowski et al [5] but is in agreement with more recent results [1,4,7,8]. Although they are regarded as reliable indicators of HTLV exposure in population screening, Koprowski et al [6] suggest that commercial ELISA tests against disrupted virions are insensitive cornOffprint requests to: D. A. S. Compston pared with assays detecting antibody to the major core protein p24 of HTLV I alone because the antibodies are present in low titre, cross-reactive and only present sporadically in the course of the disease.…”
contrasting
confidence: 99%
“…Sirs: It has recently been claimed that a novel retrovirus may be involved in the aetiology of multiple sclerosis [5]. Serological tests have demonstrated antibodies to human T-cell lymphotropic viruses (HTLV) I, II and III (HIV) in up to 70% of patients and molecularly cloned probes have revealed the existence of HTLV-I related nucleotide sequences in cells from the cerebrospinal fluid of some affected individuals.…”
mentioning
confidence: 99%
“…In particular, the association of human immunodeficiency virus (HIV) in AIDS encephalopathy and human T-celllymphotropic virus I (HTLV-1) in tropical spastic paraparesis (TSP) has given support to the hypothesis that human retroviruses may also be involved in MS. Moreover, following serological andin situ hybridization studies a possible relationship between HTL V-I related viruses and MS has been suggested [8,13]. However, other investigators obtained negative results and could not confirm this association (5,7].…”
Section: Introductionmentioning
confidence: 99%
“…The seven cases of MS associated with male HD patients included a mother, two fathers (one of whom also had a sister with MS), the remainder being relatives by marriage rather than direct blood relatives. Recent evidence has implicated an (as yet) unidentified retrovirus in MS (Koprowski et al, 1985).…”
Section: Past Medical Historymentioning
confidence: 99%